Pembelajaran Fisika Dasar dan Elektronika Dasar Menggunakan Aplikasi Matlab Metode Simulink - Hutagalung, Siti Nurhabibah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
Learning about basic physics and basic electronics can be done with matlab program simulink method, by simulating basic physics formulas and basic electronics in graphical form and simulation display with simulink. Understanding of basic physics learning and basic electronics that is in electrical learning about current, voltage , electrical power. Basic physics and basic electronics learning by simulink method can help understanding to mahasisswa in comprehending lecture material in the form of simulation. Keywords: basic physics deployment, matlab, methods simulink